Is training age predictive of physiological performance changes in elite developmental rugby league players: A prospective tracking study - Booth, M.; Halaki, M.; Cobley. S.; Orr, R. (Journal of Australian Strength and Conditioning, 2019)
Individuals with a higher pre-study rugby league training age exhibited a greater improvement in performance measures. Pre-study resistance and cardiovascular training ages may have been inadequate to identify relationships with performance enhancements in this population.